Infective endocarditis with systemic bacterial embolism caused by Staphylococcus aureus in a free-ranging Amami rabbit (Pentalagus furnessi). (February 2023) - Konnai, Masaki; Yamamoto, Masami; Ito, Keiko; Yamabe, Hanae; Kishimoto, Takuya E; Aoki, Hiroshi; Machida, Yukino; Michishita, Masaki; Haritani, Makoto; Yoshimura, Hisashi
ABSTRACT: The Amami rabbit ( Pentalagus furnessi ) is found only on the two islands of Amami-Ōshima and Tokunoshima in southwest Japan. It has a primitive appearance and ecology, is an evolutionarily valuable animal and has been assigned to the International Union for Conservation of Nature Red List of Threatened Species. We describe a case with mild purulent wounds on the distal digital skin of both forelimbs and multiple nodular lesions in various organs, including the heart and kidney. Microscopically, the heart lesions were characterized by disruption of the mitral valve and multifocal myocardial necrosis and abscesses due to infection with gram-positive cocci. Similar bacterial infarctions were also found in other organs, including the kidneys. The bacteria were identified as Staphylococcus aureus by immunohistochemical and molecular biological examinations. This first report of infective endocarditis and systemic infarctions caused by S. aureus in an Amami rabbit indicates the importance of monitoring purulent injuries, even if mild, to prevent secondary infections in this species.